Fulfillment of Human Rights of People with Disabilities in the Implementation of Regional Elections through Increasing the Role of Regional Election Commissions to Strengthen Local Democracy - Riwanto, Agus; Isharyanto, Isharyanto; Maharani, Andina Elok Puri; Kusumo, Ayub Torry Satriyo (Law Research Review Quarterly, 2018)
The Regional Election Commission has the responsibility to increase the participation of disabled voters in local legislative elections. Democratic elections at the local level are characterized by the enthusiasm of disability voters in the election. The purpose of this paper is to map out legislation on the protection and respect of disability voters, to explore some of the constraints facing electoral voters in the election, and to examine the policies and obstacles faced by the The Regional Election Commission in an effort to increase voter participation in disability. This study uses socio-legal research methods, ie research that is interdisciplinary to provide a meeting room between the science of law and the sciences outside the law. The results show that, there are international law and national laws. Barriers facing disability voters include: theoretically there is no uniformity about the disability study; the culture of the people who tend to stigmatize the bad, not counting the right to vote; lack of accurate data of disability voters. The policies made by the The Regional Election Commission in increasing the participation of disability voters are: to implement Article 1 number 25 and Article 149 of Law No. 8 of 2012 on General Election of Members of DPR, DPD and DPRD. While the obstacles, namely: the weakness of family and community awareness; lack of human resources capacity of voter registration officers and data on the List of Potential Voters of Electoral Residents (DP4) does not mention information about disability.